The Effectiveness of Somatization in Communicating Distress in Korean and American Cultural Contexts - Choi, Eunsoo; Chentsova-Dutton, Yulia; Parrott, W. Gerrod (Frontiers in Psychology, 2016)
Previous research has documented that Asians tend to somatize negative experiences to a greater degree than Westerners. It is posited that somatization may be a more functional communication strategy in Korean than American context. We examined the effects of somatization in communications of distress among participants from the US and Korea. We predicted that the communicative benefits of somatic words used in distress narratives would depend on the cultural contexts. In Study 1, we found that Korean participants used more somatic words to communicate distress than US participants. Among Korean participants, but not US participants, use of somatic words predicted perceived effectiveness of the communication and expectations of positive reactions (e.g., empathy) from others. In study 2, we found that when presented with distress narratives of others, Koreans (but not Americans) showed more sympathy in response to narratives using somatic words than narratives using emotional words. These findings suggest that cultural differences in use of somatization may reflect differential effectiveness of somatization in communicating distress across cultural contexts.